2017
DOI: 10.1063/1.4975020
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ion motion on linear Landau damping

Abstract: This version is available at https://strathprints.strath.ac.uk/59829/ Strathprints is designed to allow users to access the research output of the University of Strathclyde. Unless otherwise explicitly stated on the manuscript, Copyright © and Moral Rights for the papers on this site are retained by the individual authors and/or other copyright owners. Please check the manuscript for details of any other licences that may have been applied. You may not engage in further distribution of the material for any pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The theory of nonlinear damping (growth) of Langmuir waves in collisionless inhomogeneous plasma was developed by Karpman et al [37] Several important studies have been carried out on the effect of the plasma parameters on Landau damping of plasma waveguides. [38][39][40] Xu et al [38] investigated the effects of ion motion on Landau damping aided by one-dimensional Vlasov-Poisson simulation. It was shown that the ion motion can significantly change the development of linear Landau damping.…”
Section: Introductionmentioning
confidence: 99%
“…The theory of nonlinear damping (growth) of Langmuir waves in collisionless inhomogeneous plasma was developed by Karpman et al [37] Several important studies have been carried out on the effect of the plasma parameters on Landau damping of plasma waveguides. [38][39][40] Xu et al [38] investigated the effects of ion motion on Landau damping aided by one-dimensional Vlasov-Poisson simulation. It was shown that the ion motion can significantly change the development of linear Landau damping.…”
Section: Introductionmentioning
confidence: 99%
“…This can lead us to assume that ion dynamics could be neglected and only the electron evolution should be computed. However, it is important to remember that small changes of the ion particle density influence the resolution of the Poisson's equation, which modify the electron motion due to their low mass, specially in the analysis of long times [21,101]. So, if there are enough computational resources, it is advisable to advance both species, also with the same time step, to not perturb the problem and to obtain a more accurate electric field.…”
Section: Two Charged Species With Self-consistent Electric Fieldmentioning
confidence: 99%
“…A similar rotational ion dynamics is expected, because the electric field also influence the evolution of this species. However, slow ion variation, as well as the fast motion of the electrons, can give rise situations where electric field changes its sign and ions have not reached a periodical behaviour, creating a non-circular dynamics for this heavy species, which may end up affecting the evolution of electrons due to the changes in the charge density [101]. This is better appreciated in figure 3.10, where the trajectory of the maximum point of f α is pictured.…”
Section: Two Charged Species With Self-consistent Electric Fieldmentioning
confidence: 99%
See 2 more Smart Citations